A New Type of Film Driver. (1981) - Murata, Masato; Akitake, Shohei; Yamaguchi, Hitoshi; Sasaki, Hajime; Otani, Shiro
Abstract : A new type of film driver (NFD) has been developed using thin film integrated circuits technologies. The realized driver was one-tenth as small as that of a conventional driver in volume. The NFD has employed the tantalum nitride (Ta2 N) thin film resistors with low TCR values in order to achieve high accuracy. The NFD was housed in a hermetically-sealed metal case with a size of 39 × 26 × 6 mm. Resistors of NFD circuits were adjusted by laser trimming. DC levels of the transistor circuits, were adjusted by functional laser trimming. When the developed NFD is operated at medium output voltage of 4 Vp-p for 5 years at circumstance temperature of 40℃, the resistance change of the resistors which control the accuracy of the output voltage is predicted to be less than 0.05%, which corresponds to the drift of the output level within 2 mV.